Are Older Workers Willing to Learn? - Jens Ruhose; Stephan L. Thomsen; Insa Weilage (Global Labor Organization (GLO), 2020)
Adult education can mitigate the productivity decline in aging societies if older workers are willing to learn. We examine a generous partial retirement reform in Germany that led to a massive increase in early retirement. Using county-level administrative data on voluntary education activities, we employ a difference-in-differences approach for identification. The estimates show a strong increase in participation in adult education, specifically in cognitively demanding courses, for early retirees who would have continued working in the absence of the reform. This supports the notion of an intrinsic willingness of older individuals to acquire skills and abilities independent of financial incentives.
Keywords: J14; J24; J26; 330; partial retirement; early retirement; older workers; adult education; generalized difference-in-differences